[Retracted] Debt Maturity Structure and Firm Life Cycle: Empirical Evidence from Asean Countries - Juliana, Rita (Jurnal Akuntansi dan Bisnis, 2023)
This article was retracted due to the following reasons: Article: Debt Maturity Structure and Firm Life Cycle: Empirical Evidence from ASEAN Countries. Volume 23 Number 2 Author: Rita Juliana The publisher has retracted this article with the reason of duplicate submission. Author of the paper agreed with the reason.